Pengaruh Pendidikan Kesehatan Terhadap Tingkat Pengetahuan dan Sikap Siswi dalam Penanganan Dismenorea di SMP Negeri 1 Mlati - Fidya Tri Prananti; Sri Lestari (Lembaga Pengembangan Kinerja Dosen, 2026)
Adolescence is a transitional period from childhood to adulthood, typically characterized by puberty between the ages of 12 and 14 years, accompanied by physical, social, and emotional changes. In adolescent girls, reproductive maturation is marked by the onset of menstruation as an early indicator of maturity, which is often accompanied by menstrual disorders such as dysmenorrhea. Dysmenorrhea, or menstrual pain, is a common condition among adolescent girls and may interfere with academic activities and overall quality of life. Inadequate knowledge and inappropriate attitudes toward its management often lead adolescents to neglect symptoms or adopt suboptimal pain management strategies. This study aims to examine the effect of health education on female students’ knowledge and attitudes regarding dysmenorrhea management at SMP Negeri (State Junior High School) 1 Mlati. A pre-experimental study with a one-group pretest-posttest design was employed. The study population consisted of all eighth-grade female students, with a sample of 66 participants selected through purposive sampling based on the inclusion criteria of having experienced menarche and being willing to participate throughout the study. Data were analyzed using the Wilcoxon nonparametric statistical test to assess differences before and after the health education intervention. The results of the Wilcoxon test demonstrated a significant improvement in both knowledge (p = 0.000) and attitudes (p = 0.002) following the intervention. It can be concluded that health education has a significant effect on improving female students’ knowledge and attitudes toward dysmenorrhea management. Future researchers are encouraged to develop more innovative educational media by utilizing social media platforms such as Instagram and TikTok to enhance the effectiveness and attractiveness of educational interventions.